L' évadée - Woolrich, Cornell 1903-1968; Michelet, Michel 1894-1995 (Artus Films, 2012)
"Returning a lost wallet gains unemployed veteran Chuck Scott a job as chauffeur to Eddie Roman, a seeming gangster whose enemies have a way of meeting violent ends. The job proves nerve-wracking, and soon Chuck finds himself pledged to help Eddie's lovely, fearful, prisoner-wife Lorna to escape. The result leaves Chuck caught like a rat in a trap, vainly seeking a way out through dark streets. But the real chase begins when the strange plot virtually starts all over again ..." [amazon.de]
Original: USA 1946
suppléments: "William Irish and the chase" par Stéphane Bourgoin (18 min) ; court-métrage "l'héroine" de Mireille Huchon et Bernard Laborde (30 min) ; diaporama de photos ; bande-annonce
Bildformat 1.33:1 (4:3)
Keywords: Film; DVD-Video